Transcriptional Coactivators: Driving Force of Plant Immunity - Khan, Muhammad Saad Shoaib; Islam, Faisal; Chen, Huan; Chang, Ming; Wang, Daowen; Liu, Fengquan; Fu, Zheng Qing; Chen, Jian (Frontiers in Plant Science, 2022)
Salicylic acid (SA) is a plant defense signal that mediates local and systemic immune responses against pathogen invasion. However, the underlying mechanism of SA-mediated defense is very complex due to the involvement of various positive and negative regulators to fine-tune its signaling under pathogen attacks. Upon pathogen infections, elevated level of SA promotes massive transcriptional reprogramming in which Nonexpresser of PR genes 1 (NPR1) acts as a central hub and coactivator in defense responses. Recent findings show that Enhanced Disease Susceptibility 1 (EDS1) also functions as a transcriptional coactivator and stimulates the expression of PR1 in the presence of NPR1 and SA. Moreover, EDS1 stabilizes the NPR1 protein level, while NPR1 sustains the EDS1 expression during pathogenic infection. The interaction of NPR1 and EDS1 coactivators initiates transcriptional reprogramming by recruiting cyclin-dependent kinase 8 (CDK8) in the Mediator complex to control immune responses. In this review, we highlight the recent breakthroughs that considerably advance our understanding of how transcriptional coactivators interact with their functional partners to trigger distinct pathways to facilitate immune responses, and how SA accumulation induces dynamic changes in NPR1 structure for transcriptional reprogramming. In addition, the function of the Mediator complex as a transcriptional coactivator, and its participation in SA-mediated plant immunity are also discussed in light of recent discoveries. Taken together, transcriptional coactivators are essential regulators of plant defense pathways, and play a crucial role in coordinating plant immune responses during plant-pathogen interactions.